The pension system of the Republic of Kazakhstan: current status and future prospects - Kaliyeva, M. E. (Journal of Economic Research & Business Administration, 2015)
The pension system is a major and pressing social and economic problem in any country. Sovrenmennaya pension system of Kazakhstan - composes one of the main social and economic security and an important investment tool in the economy. Directions for reform pensions based on the reduction of public spending, while ensuring public pension capital. Reform of the pension system in Kazakhstan was the first held in the CIS, so the experience of our country can be an example of pension reforms in other countries, yet recent socio-economic developments require making amendments to the pension system. Including an important issue in dealing with our system to make changes to the retirement age given the trend of an aging population, form a reserve lever or regulatory body to regulate the investment of pension assets, etc.